Karakteristik Dewan Direksi dan Pengaruhnya terhadap Kinerja Keuangan Perusahaan - Zulkarnain Zulkarnain; Wuri Mirawati (Cakrawala Repositori IMWI, 2019)
This study examines the impact of board characteristic on firm financial performance. Firm financial performance is measured by ROA. Board characteristic are defined by gender, age, and nationality. This study employs publicly available data from annual reports of a sample of 50 firm observation. Using multiplied linear regression analysis with hypotheses test of t statistics, this study finds gender and age, partially, had no significant impact on firm financial performance. The foreign board membership on the other hand, partially, had positive and significant impact on firm financial performance.